Impact of the Human Immunodeficiency Viruses Status on Outcomes in Patients Hospitalized With Acute Pancreatitis: A Propensity-Matched Analysis. Issue 9 (October 2020) - Jiang, Yi; Rodgers, Brandon; Chowdhury, Salil; Ali, Hasan; Ahlawat, Sushil
Abstract : Objectives: We aimed to examine the clinical characteristics and outcomes of patients admitted for acute pancreatitis (AP) in the population with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS). Methods: The National Inpatient Sample from 2010 to 2014 was used to identify adult patients admitted with AP. Patients were grouped based on the HIV status. Primary outcomes were mortality, length of stay (LOS), disposition and total hospitalization charges. Secondary outcomes included acute kidney injury, septic shock, respiratory failure and pancreatic procedures. Results: After matching and weighting, a total of 14, 152 HIV-positive patients (6904 with AIDS and 7248 with asymptomatic HIV [aHIV]) with AP were identified. Acute pancreatitis with AIDS were associated with a higher rate of acute kidney injury, longer LOS, higher hospitalization charges, and less routine disposition compared with HIV-negative AP. Patients with aHIV had less septic shock, shorter LOS, and less hospitalization charges compared with HIV-negative patients and less respiratory failure, shorter LOS, and less hospitalization charges compared with AIDS patients. Conclusions: Patients admitted for AP with AIDS have worse outcomes. On the contrary, aHIV status was not only associated with better outcomes when compared with AIDS, but to HIV-negative status as well. Abstract : Supplemental digital content is available in the text.